2019
DOI: 10.1158/1541-7786.mcr-19-0654
|View full text |Cite
|
Sign up to set email alerts
|

Functional Loss of ATRX and TERC Activates Alternative Lengthening of Telomeres (ALT) in LAPC4 Prostate Cancer Cells

Abstract: A key hallmark of cancer, unlimited replication, requires cancer cells to evade both replicative senescence and potentially lethal chromosomal instability induced by telomere dysfunction. The majority of cancers overcome these critical barriers by upregulating telomerase, a telomere-specific reverse transcriptase. However, a subset of cancers maintains telomere lengths by the telomerase-independent Alternative Lengthening of Telomeres (ALT) pathway. The presence of ALT is strongly associated with recurrent can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Further confirming the role of ATRX as an ALT repressor, ATRX knockdown has been shown to induce ALT activity in cells of mesenchymal origin [30]. However, ATRX depletion does not promote ALT activity in all cell types [31,32] suggesting that ATRX LoF alone is not sufficient to induce ALT and that additional, as yet unidentified mechanisms are also needed. Reinforcing the notion that ALT arises as a result a combination of ATRX loss and other factors, it has recently been shown that during the immortalisation process, ATRX loss results in a progressive chromatin de-compaction and a gradual induction of telomere replication dysfunction which triggers an adaptive response eventually resulting in ALT activation [33].…”
Section: Biology Of Telomere Maintenancementioning
confidence: 90%
“…Further confirming the role of ATRX as an ALT repressor, ATRX knockdown has been shown to induce ALT activity in cells of mesenchymal origin [30]. However, ATRX depletion does not promote ALT activity in all cell types [31,32] suggesting that ATRX LoF alone is not sufficient to induce ALT and that additional, as yet unidentified mechanisms are also needed. Reinforcing the notion that ALT arises as a result a combination of ATRX loss and other factors, it has recently been shown that during the immortalisation process, ATRX loss results in a progressive chromatin de-compaction and a gradual induction of telomere replication dysfunction which triggers an adaptive response eventually resulting in ALT activation [33].…”
Section: Biology Of Telomere Maintenancementioning
confidence: 90%
“…Low-grade and high-grade prostate intraepithelial neoplasia (PIN) lesions develop from normal prostate epithelium through the loss of phosphatase and the tensin homolog (PTEN) , NK3 Homeobox 1 ( NKX3.1) , overexpression of MYC proto-oncogene, B-cell lymphoma 2 ( BCL-2), and the glutathione S-transferase pi 1 gene ( GSTP1), accompanied with Speckle Type BTB/POZ Protein ( SPOP) mutation and Transmembrane Serine Protease 2- ETS-related gene ( TMPRSS2-ERG) fusion [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Further loss of the retinoblastoma protein ( RB1) , along with telomerase activation and frequent Forkhead Box A1 ( FOXA1) mutation, leads to the development of prostate adenocarcinoma from the advanced PIN lesion [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Further molecular aberrations including the loss of SMAD Family Member 4 ( SMAD4) , AR corepressors, mutations in AR, FOXA1, BRCA1/2, ATM, ATR, and RAD51 accompanied with the gain of function of the AR coactivator, CXCL12, CXCR4, RANK-RANKL, EMT, BAI1 , and EZH2 lead to the development of metastatic prostate cancer [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Cellular and Molecular Progression Of Prostate Cancermentioning
confidence: 99%
“…Recently, some authors succeeded in switching telomerase-positive cancer cell lines into ALT-active ones [63]. The study of the epigenetic modification of telomeres, before and after the switch, could be useful for elucidating the real chromatin modifications associated with ALT.…”
Section: Discussionmentioning
confidence: 99%